THE RELATIONSHIP BETWEEN THE INTAKE OF ENERGY, PROTEIN, IRON, AND VITAMIN C WITH HEMOGLOBIN STATUS IN PULMONARY TUBERCULOSIS OUTPATIENTS - Muzakar; Susyani; Listrianah; Sriwiyanti (International Journal of Research -GRANTHAALAYAH, 2022)
Background: Pulmonary Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis with a treatment period of 6 months to more than one year. The prevalence of pulmonary TB in Indonesia in 2013 was 40% and in South Sumatra in 2018 was 40%. The management of pulmonary TB patients involves several things, namely adequate rest, anti-tuberculosis drug (ATD) therapy, and adequate food intake (sufficient) to recover the patients' pulmonary TB. Purpose in this study investigated the relationship between energy and protein intake, iron, and vitamin C with Hemoglobin (Hb) status in pulmonary TB patients. Method: The type of research used is an observational analytic study with a cross sectional research design with a sample size of 50 human subjects. Participants were selected according to the inclusion criteria and interviewed using a prepared questionnaire. Participants' food intake was obtained using a 24-hour food recall method for 3 days. Body weight, height, and blood pressure were measured. Blood samples were taken to determine the participants' hemoglobin levels Result: There was no relationship between the Hb value and energy intake (p = 0.658) and protein (p = 0.357), while there was a relationship between the Hb value and iron intake (p = 0.012) and vitamin C (p = 0.001). Conclusion: The results of statistical tests showed a relationship between the Hb value with iron and vitamin C intake, while the energy and protein intake had no relationship with the Hb level in pulmonary TB patients.